Tinjauan terhadap Metode Ekonometrika Lanjutan - Aulia F., Telisa (UI Scholars Hub, 2003)
Econometric models have been played an increasingly important role in empirical analysis in economics. This paper provides an overview on some advanced econometric methods that increasingly used in empirical studies. A panel data combines features of both time series and cross section data. Because of increasing availability of panel data in economic sciences, panel data regression models are being increasingly used by researcher. Related to panel data model, there are some methods that will be discussed here such as fixed effect and random effect. A new approach to panel data that developed by Im, Shin, and Pesaran (2002) for testing unit root in heterogenous panel is included.in this overview. When we work with time series data, there are many problems that we must handle, most of them are unit root test, cointegration among non stationary variables, and autoregressive conditional heteroscedasticity. Provided these problems, author also review about ADF and Philips-Perron test. An approch to cointegration analysis developed by Pcsaran (1999), ARCH and GARCH model are also interesting to be discussed here. Bayesian econometric, that less known than classical econometric, is included in this overview. The genetic algorithm, a relatively new method in econometric, has been increasingly employed the behavior of economic agents in macroeconomic models. The genetic algorithm is based on the process of Darwin's Theory of Evolution. By starting with a set of potential solutions and changing them during several iterations, the Genetic Algorithm hopes to converge on the most 'fit' solutions.